Capturing the experiences of patients across multiple complex interventions: a meta-qualitative approach. Issue 9 (8th September 2015) - Webster, Fiona; Christian, Jennifer; Mansfield, Elizabeth; Bhattacharyya, Onil; Hawker, Gillian; Levinson, Wendy; Naglie, Gary; Pham, Thuy-Nga; Rose, Louise; Schull, Michael; Sinha, Samir; Stergiopoulos, Vicky; et al.
Abstract : Objectives: The perspectives, needs and preferences of individuals with complex health and social needs can be overlooked in the design of healthcare interventions. This study was designed to provide new insights on patient perspectives drawing from the qualitative evaluation of 5 complex healthcare interventions. Setting: Patients and their caregivers were recruited from 5 interventions based in primary, hospital and community care in Ontario, Canada. Participants: We included 62 interviews from 44 patients and 18 non-clinical caregivers. Intervention: Our team analysed the transcripts from 5 distinct projects. This approach to qualitative meta-evaluation identifies common issues described by a diverse group of patients, therefore providing potential insights into systems issues. Outcome measures: This study is a secondary analysis of qualitative data; therefore, no outcome measures were identified. Results: We identified 5 broad themes that capture the patients' experience and highlight issues that might not be adequately addressed in complex interventions. In our study, we found that: (1) the emergency department is the unavoidable point of care; (2) patients and caregivers are part of complex and variable family systems; (3) non-medical issues mediate patients' experiences of health and healthcare delivery; (4) the unanticipated consequences of complex healthcare interventions are often the most valuable; and (5) patient experiences are shaped by the healthcare discourses on medically complex patients. Conclusions: Our findings suggest that key assumptions about patients that inform intervention design need to be made explicit in order to build capacity to better understand and support patients with multiple chronic diseases. Across many health systems internationally, multiple models are being implemented simultaneously that may have shared features and target similar patients, and a qualitative meta-evaluation approach, thus offers an opportunity for cumulative learning at a system level in addition to informing intervention design and modification.